The Use of Students’ Feedback Indicators in Programme Quality Assessment in Sri Lankan Universities - Weligamage, S.S. (My University, 2015)
The need for assurance of quality in higher education programs has continued to draw the attention of stakeholders globally and in Sri Lanka. The key purpose of reviews of educational programmes is to evaluate the overall quality of education provided by a specific degree programme. This activity is based on the perception of students on their learning experience and achievements. However, there is no established formal mechanism to assess and evaluate the students’ educational and learning experience in the Sri Lankan context. The objectives of this study were a) develop a set of applicable indicators to evaluate programs in the Sri Lankan context, and b) to apply developed students’ learning experience indicators to evaluate selected degree programme performance. Indicators were selected based on a review of literature on current international practices of evaluation of study programs. Fourteen indicators were identified and included in to seven categories as; i) curriculum design; ii) teaching and learning; iii) assessment methods; iv) generic skills; v) academic guidance and counseling; vi) support and resources, and vii) learning community. Applicability of selected indicators was validated using responses to a structured questionnaire by 748 undergraduate students from seven universities that offered undergraduate programs on management. Validated indicators were subsequently used to evaluate selected six undergraduate study programmes through a survey of a total of 249 undergraduates selected from two universities. The findings support the use of students’ educational and learning experience based indicators in evaluating and comparing the performance of degree programmes. The indicators identified and the procedures can be used in identifying areas for improvement at programme level and faculty level, or comparing performance within programmes to identify the weaknesses and good practices.
Keywords: Learning experiences; perception based Indicators; performance evaluation; teaching and learning; undergraduate programs